In vivo genome editing using Staphylococcus aureus Cas9 - Ran, F. Ann (Nature, 2015)
The RNA-guided endonuclease Cas9 has emerged as a versatile genome-editing platform. However, the size of the commonly used Cas9 from Streptococcus pyogenes (SpCas9) limits its utility for basic research and therapeutic applications that employ the highly versatile adeno-associated virus (AAV) delivery vehicle. Here, we characterize six smaller Cas9 orthologs and show that Cas9 from Staphylococcus aureus (SaCas9) can edit the genome with efficiencies similar to those of SpCas9, while being >1kb shorter. We packaged SaCas9 and its sgRNA expression cassette into a single AAV vector and targeted the cholesterol regulatory gene Pcsk9 in the mouse liver. Within one week of injection, we observed >40% gene modification, accompanied by significant reductions in serum Pcsk9 and total cholesterol levels. We further demonstrate the power of using BLESS to assess the genome-wide targeting specificity of SaCas9 and SpCas9, and show that SaCas9 can mediate genome editing in vivo with high specificity.